2019
DOI: 10.24191/ijsms.v4i1.8180
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates’ Speaking Anxiety in English as Second Language (ESL) Classrooms

Abstract: Many students exhibit fear of speaking in English in the English as Second Language (ESL) classrooms. Additionally, there are limited studies in this area of concern among the undergraduates in Sarawak. Hence, this study aimed to identify the students‟ anxiety level towards speaking English based on four components, namely communication apprehension, test anxiety, fear of negative evaluation, and comfort in using English in the classrooms. This study also examined whether there is any significant difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…The dominant factor contributing to this issue was communication apprehension for high and moderate anxiety learners, while test anxiety was observed in low anxiety learners. Another noteworthy study on this issue can also be observed in Long, Yih, and Lin (2019) on undergraduate students from two public institutions of higher learning in Sarawak. While this study reported that the students generally experienced an average of speaking anxiety, which was a similar finding to Miskam and Saidalvi's (2019) study, one interesting observation was that female undergraduate experienced a significantly higher level of speaking anxiety compared to their male counterparts.…”
Section: Public Speaking Anxietymentioning
confidence: 92%
See 1 more Smart Citation
“…The dominant factor contributing to this issue was communication apprehension for high and moderate anxiety learners, while test anxiety was observed in low anxiety learners. Another noteworthy study on this issue can also be observed in Long, Yih, and Lin (2019) on undergraduate students from two public institutions of higher learning in Sarawak. While this study reported that the students generally experienced an average of speaking anxiety, which was a similar finding to Miskam and Saidalvi's (2019) study, one interesting observation was that female undergraduate experienced a significantly higher level of speaking anxiety compared to their male counterparts.…”
Section: Public Speaking Anxietymentioning
confidence: 92%
“…Stress in public speaking, specifically among undergraduate students, has been extensively explored by researchers over the years (Zulkurnain & Kaur, 2014;Evans, Clinton, Cookson, Brown & Woods, 2017;Long, Yih & Lin, 2019). This phenomenon has also been studied across different age groups, such as high school students (Katz, 2016) and working adults (Mellifont, Smith-Merry & Scanlan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, as Rafek et al (2014) highlighted, gender is an insignificant factor in CA, supported by McCroskey (1984), who explained that CA has minimal connection with gender. Based on the findings from several studies on different contexts towards gender roles in the CA (Abdullah, 2014;Kimberley et al, 2020), a common trend was found where females present a higher level of CA than males. However, most studies needed to test an extensive enough number of respondents to generalise this assumption.…”
Section: Oral Communication Apprehension and Workplace Settingmentioning
confidence: 99%
“…Most studies reported that tertiary students experienced a moderate English CA level (Ireland, 2020;Miskam & Saidalvi, 2018). Moreover, concerning gender and CA level, most studies reported that females were more apprehensive than males (Kimberley et al, 2020;Loureiro et al, 2020). Pragash et al (2020) concluded no significant difference between gender and CA among 450 Malaysian undergraduates who responded from several public universities.…”
Section: Oral Communication Apprehension and Workplace Settingmentioning
confidence: 99%
See 1 more Smart Citation